Os limites do direito de privacidade na sociedade de informação no âmbito contratual - Leite, Olga Fernandes de Moura (2018)
The right to privacy is a sensitive subject in the information society. There are those who argue that this right is dead, since there is no expectation that with so much information available there can be an absence of external interference in private life. People are constantly being watched on a voluntary or involuntary basis. Every day access to personal information is granted, those derived from self-exposure as well as those obtained by online behavioral patterns, when uncovering interests, social circle, needs, living standards, daily routes, location, etc. This dissertation seeks to study the right to privacy in postmodernity, making a historical immersion of fundamental rights and personality rights, as well as to study the comparative law. In order to understand how the right to privacy is embedded in the information society, an analysis will be made of the main concepts of the internet, of service providers, their responsibilities and in particular of the tools used to determine a browsing session, but that can also be used to abusively increase prices of services or products or to conduct practices known as geo-blocking and geo-pricing. In the online world, then, a new concern arises, the protection of data, which derives from the right to privacy. Therefore, the limits of the right to privacy, its coexistence with the right to freedom of speech, right to information, free access and technological development will be studied. In relation to data protection, the European Directives, the Civil Rights Framework for the Internet, the novel Law 13.709/2018 and the forms of protection of the right to privacy will be analyzed. Since in most cases a contractual relationship is formed within the internet, the right to privacy in the contractual scope will also be studied, in accordance with the principles of objective good faith, especially, to verify if there is breach of attached duties with the abusive increase of the price within a proposal, using information that can be obtained, for example, with cookies. Thus, the dissertation seeks to verify the legal consequences of this practice or of the sale or use of data without consent, of the loss of this data, to analyze contractual clauses in particular of the End Users License Agreements, analyzing other specific electronic contracts, such as click-wraps, browse-wraps, the privacy policies of various websites and applications. It will also be done a jurisprudential analysis. Finally, this work seeks to conceptualize the wrongful act, the limits of the right to privacy in the information society in the contractual scope